Teachers' perceptions of critical thinking and mathematical literacy in main school PISA 2022 regional survey Yogyakarta, Indonesia - Kintoko, Kintoko; Waluya, St. Budi; Junaedi, Iwan; Dewi, Nuriana Rachmani (Edelweiss Applied Science and Technology, 2024)
To form critical citizens, integrating critical thinking into the school curriculum is a must. Critical thinking is considered a vital skill that can help students tackle problems effectively, improve academic achievement and develop rational thinking. However, there is no agreement among teachers on the definition of this concept or the best way to train students to apply it, especially at the basic education level. Therefore, through a qualitative research approach, this study aims to uncover the views of junior secondary school teachers in the PISA 2022 Main Survey in Yogyakarta, Indonesia, regarding the concept of critical thinking and Mathematical Literacy. Six teachers working in the three schools that were the subject of this survey were interviewed using a semi-structured interview method. Through thematic analysis, this study sought to identify, analyze and report the main findings from the interviews. The results showed that the teachers recognized the importance of reasoning mapping, group discussions and active learning as practices that promote critical thinking and mathematical literacy among students. Although they had previously been exposed to these concepts through project-based learning and 'Philosophy for Kids', they indicated the need for further support through peer learning and the implementation of the 'Philosophy for Kids'.